2014
DOI: 10.4314/ahs.v13i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of family dynamics on adherence to highly active antiretroviral therapy among people living with HIV/AIDS at a tertiary hospital in Osogbo, south-west Nigeria

Abstract: Background: Adherence to highly active antiretroviral therapy (HAART) has been proven to be the only effective treatment for HIV/AIDS worldwide. Good adherence to HAART might require good family support. Objective: To determine the family dynamics and social support of people living with HIV/AIDS (PLWHA) and its roles on HAART adherence at an ARV treatment clinic in Osogbo, Nigeria Method: Descriptive cross-sectional study. Consenting PLWHA on HAART were interviewed using pre-tested semistructured questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Consistent with previous studies, it was shown in this study that adherence to HAART can be promoted by family and friend's support (Afolabi, Afolabi, Afolabi, Odewale, & Olowookere, 2014;Stubbs, Micek, Pfeiffer, Montoya, & Gloyd, 2009). Family and friends support helps to develop confidence in oneself and in taking HAART medication, brought about healing, and built in patients a conviction to live.…”
Section: Psychological Supportsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies, it was shown in this study that adherence to HAART can be promoted by family and friend's support (Afolabi, Afolabi, Afolabi, Odewale, & Olowookere, 2014;Stubbs, Micek, Pfeiffer, Montoya, & Gloyd, 2009). Family and friends support helps to develop confidence in oneself and in taking HAART medication, brought about healing, and built in patients a conviction to live.…”
Section: Psychological Supportsupporting
confidence: 92%
“…Various studies, including the present one, show that stigma/discrimination is still prevalent in many on-reserve communities with many people denying the presence of HIV (Goodyear & Loutfy, 2015; Ministry of Health Living and Sport, 2010) and either not wanting to care for or neglecting patients altogether (Afolabi et al, 2014). Due to the fear of stigma/discrimination, most HIV-infected patients do not return to their communities.…”
Section: Stigma and Discriminationmentioning
confidence: 76%
See 2 more Smart Citations
“…Social support networks inform of greater support from families, friends and communities is linked to better health. [25][26][27] In conclusion, because barriers to medication adherence are complex and varied, solutions to improve adherence must be multifactorial, the finding from our study stresses the importance of functional family and strong family support as important factors influencing medication adherence among hypertensive patients. We therefore recommended based on the outcome of this study that family dynamics should be thoroughly verified in each of physicians' consultation before prescribing medications so as to improve adherence to medications and each consultation should be used to advocate for strong family tie.…”
mentioning
confidence: 99%